The performances of partial shading adjuster for improving photovoltaic emulator - Razman Ayop; Chee Wei Tan; Syed Norazizul Syed Nasir; Mohd Zaki Daud; Lau Kwan Yiew; Norjulia Mohamad Nordin; Abba Lawan Bukar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
A photovoltaic (PV) emulator (PVE) is essential equipment for the research and diagnostic of PV generation. It is a convenient, highly efficient, and low-cost approach when compared to controllable light sources. Nonetheless, the implementation of the partial shading capability in a PVE is highly limited in terms of efficiency, computation burned, number of power converters, and flexibility to change in the ambient condition. This paper proposes a partial shading adjuster for a PVE that can overcome the aforementioned limitations. The adjuster is applicable to the conventional PVE since it is based on an algorithm that can be added to the controller of the PVE. By adding the adjuster, the conventional PVE can emulate partial shading. The partial shading adjuster is added into a PVE that uses the direct referencing control strategy with the buck controller regulated by the proportional-integral controller. The results show that the PVE maintains its accuracy and produces a stable output voltage and current during the load changes when the adjuster is added. In conclusion, the proposed partial shading adjuster able to improve th